1980
DOI: 10.1128/aem.40.2.358-364.1980
|View full text |Cite
|
Sign up to set email alerts
|

Heat damage to the chromosome of Escherichia coli K-12

Abstract: The folded chromosome or nucleoid of Escherichia coli was analyzed by lowspeed sedimentation in neutral sucrose gradients after-in vivo heat treatment. Heat treatment of cultures at 50°C for 15, 30, and 60 min resulted in in vivo association of the nucleoids with cellular protein. Structural changes, determined by the increase in speed dependence of the nucleoids from heated cells, also occurred. These changes were most likely due to the unfolding of the typical compact nucleoid structure. The nucleoids from h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…An important component affected by the temperature stress is the DNA molecule, e.g. the heat induces breaks in the DNA strain (Pellon et al 1980;Pellon and Gomez 1981). As a reaction, many micro-organisms produce heat shock proteins that are known to suppress the inactivation of several metabolic macromolecules (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…An important component affected by the temperature stress is the DNA molecule, e.g. the heat induces breaks in the DNA strain (Pellon et al 1980;Pellon and Gomez 1981). As a reaction, many micro-organisms produce heat shock proteins that are known to suppress the inactivation of several metabolic macromolecules (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of a particular microbe normally takes place within a narrow range of temperatures. It has been suggested that heat principally affects the DNA by inducing the action of exo-and endonucleases resulting in multi-strand breaks in the DNA [204,205]. In E. coli, the effect of heat has been suggested to result in the denaturation of the cell wall leaving the peptidoglycan layer weakened at one or two points after which the plasma membrane ruptures [206].…”
Section: Microbial Deathmentioning
confidence: 99%
“…Cell exposure to high temperatures results, among other effects, in DNA and membrane damage ( SEDWICK and BRIDGEs 1972, WOODCOCK and GRIGG 1972, HITCHENER and EGAN 1977, TSUCHIDO et al 1985 and in induction of the HS stimulon (NEIDHARDT et al 1984, CHUANG andBLATTNER 1993). Heat treatment of Escherichia coli cells in the range of 50 "C to 52 "C induce DNA single-and double-strand breaks and changes in the sedimentation properties of the nucleoid ( SEDWICK and BRIDGES 1972, WOODCOCK and GRIGG 1972, PELLON et al 1980. DNA breaks are also present at 46 "C and even at lower temperatures (PAULING and BECK 1975).…”
mentioning
confidence: 99%